Dimethyl fumarate in multiple sclerosis: latest developments, evidence and place in therapy - Linker, Ralf; Haghikia, Aiden (Therapeutic Advances in Chronic Disease, 2016)
Dimethyl fumarate (DMF) is one of the newer additions to the armamentarium of potent immunomodulators for the treatment of relapsing-remitting multiple sclerosis (RRMS). After more than 2 years of real-world experience and more than 190,000 patients currently treated with DMF worldwide, it is a good timepoint to review the experience gathered so far and to re-evaluate the potential of this first-line oral multiple sclerosis (MS) drug. Post-hoc analyses of clinical and magnetic resonance imaging (MRI) data, some comprising more than 6 years of drug exposure including patients from the clinical trials, and the overall notion in clinical practice widely confirm the good efficacy of DMF in RRMS. Despite an overall good safety profile, it became also clear that the necessary clinical vigilance while using DMF may not be neglected. So far, four reported cases of progressive multifocal leukoencephalopathy (PML), a towering shadow over many MS therapies, warrant proper attention in newly-updated risk management plans. This review recapitulates efficacy and safety aspects of DMF therapy in relation to reported data from the pivotal clinical trials. In addition, we summarize recent insights into DMF mechanisms of action drawn from the field of basic research which may have important implications for clinical practice.
EVALuna2:22549